Opera omnia Desiderii Erasmi Roterodami Ordinis noni Tomus Quartus - Erasmus (Huygens instituut/Brill, 2003)
This thirtieth volume in Erasmus' Opera omnia (ASD) is the fourth volume within 'ordo' IX, that is the 'ordo' of the Apologies. The division into 'ordines' each 'ordo' being devoted to a specific literary or thematic category - was laid down by Erasmus himself for the posthumous publication of his works (see General introduction, ASD I, pp. x, xvii-xviii, and C. Reedijk, Tandem bona causa triumphat. Zur Geschichte des Gesamtwerkes des Erasmus von Rotterdam. Vortrage der Aeneas-Silvius-Stiftung an der Universita.t Basel, XVI, Basel/Stuttgart, 1980, p. 12 sqq., 21-22). The present volume (tom. IX, 4) contains Apologia qua respondet duabus inuectiuis Eduardi Lei; Responsio ad annotationes Eduardi Lei; Manifesta Mendacia (ed. Erika Rummel, Toronto), and Responsio ad disputationem cuiusdam Phimostomi de diuortio (ed. Edwin Rabbie, The Hague). The Editorial Board and the editors of the present volume are grateful to all libraries that kindly put books, photostats, microfilms, and bibliographical material at their disposal. On 6 May, 2002, Professor Sem Dresden, President of the Conseil international pour l'edition des reuvres completes d'Erasme from 1971-1998, died at Leiden at the age of 87. This Presidency was but one of the many official duties he carried out with such distinction. He served as rector magnificus of Leiden University, as President of the Royal Netherlands Academy of Arts and Sciences, and as chairman of many other societies and committees. His style of presiding was casual and ironical, but always very effective. Although much sought-after as chairman of various bodies in the scholarly world, his real love was for literature and art. He started his academic career at Leiden University as professor of French literature (1947-1975), after which he switched to general literature (1975-1981). His publications mirror his versatile mind: he wrote about Erasmus, Rabelais, Grotius, Proust, Valery and many others; he discussed, among other things, kitsch, the detective novel and the VIII PREFACE pleasure of reading; he devoted books to the theory of biography, humanism, creativity, symbolism, and Holocaust literature. One of Dresden's favourite authors was Montaigne whom he characterised as the 'spelende wijsgeer' (the playing philosopher). In April 2002 he was awarded the EC. Hooft prize, the Dutch national prize for literature, for his books and essays. Professor Dresden joined the Conseil international in 1965 and has also been a member of the Editorial Board. In 1977 he edited Erasmus' De contemptu mundi (ASD V, I, pp. 1-86) and in 1985 the Commentaries on Psalms 2 and 3 (ASD V, 2, pp. 81-179). We will cherish the memory or our former President for his many contributions to the Erasmus edition. His devotion to ASD and its collaborators was, as we remember, often hidden behind what he himself used to call his lightheartedness.